Is It Possible to Estimate Spanish Missing Person’s Forced and Fatal Outcomes Cases Using Socio-demographic Data? Gender, Age and Nationality - García-Barceló, Néstor (European journal on criminal policy and research, 2024)
Although research on missing persons has globally increased during the past few years, most of the studies conducted have focused on the description of socio-demographic and situational factors associated with this phenomenon. The aim of this study is to explore in-depth the relation between missing person’s socio-demographic factors and missing person’s typology and outcomes. A full 1-year sample of police recorded missing persons (n = 24,284) was extracted from the Spanish ‘Missing Persons and Unidentified Human Remains (PDyRH)’ system and a multivariate statistical approach was used. The findings of this research show that, although nationality and gender are mainly important from a descriptive level, age is the socio-demographic variable that better classifies the typology and outcome of missing person cases. These findings suggest that age is a modulating variable of this phenomenon. Thus, there is a need for the conduction of research for each specific age group focused on identifying psychosocial, criminological and geographical risk factors which could explain missing person case outcomes from a multifaceted approach. Considering previous research in the field, the findings of this research are mostly consistent with these previous studies and entail different implications, both at prevention level and in the scope of police investigations.